Drug‐induced hypersensitivity syndrome/drug reaction with eosinophilia and systemic symptoms due to lamotrigine differs from that due to other drugs. Issue 3 (21st January 2019) - Tashiro, Yasuya; Azukizawa, Hiroaki; Asada, Hideo; Niihara, Hiroyuki; Morita, Eishin; Yamauchi, Teruo; Mizukawa, Yoshiko; Kusakabe, Yoshio; Numazawa, Satoshi; Izumi, Miki; Sueki, Hirohiko; Watanabe, Hideaki
Abstract: Drug‐induced hypersensitivity syndrome (DIHS), also referred to as drug reaction with eosinophilia and systemic symptoms (DRESS), is a multi‐organ systemic drug reaction characterized by hematological abnormalities and reactivation of human herpesvirus‐6 (HHV‐6). DIHS/DRESS is typically associated with a limited number of drugs, such as the anticonvulsants. Our group has treated 12 patients for DIHS/DRESS due to lamotrigine (LTG), but their presentation differed from that of patients with DIHS/DRESS caused by other drugs. The aim of the present study was to identify significant differences between DIHS/DRESS caused by LTG versus other drugs. We retrospectively reviewed data of 12 patients with DIHS/DRESS caused by LTG and 32 patients with DIHS/DRESS due to other drugs. The increase in alanine aminotransferase level was significantly milder in the LTG group than the DIHS/DRESS group due to other drugs. The percentage of atypical lymphocytes in the blood during DIHS/DRESS was lower in the LTG group. Serum levels of lactate dehydrogenase and thymus and activation‐regulated chemokine were also lower in the LTG group. There were fewer DIHS/DRESS patients with HHV‐6 reactivation in the LTG group than in the group treated with other drugs. Lymphocyte transformation after DIHS/DRESS onset was faster in the LTG group. The two groups did not differ with respect to the interval from first drug intake to rash, white blood cell count, blood eosinophilia or DRESS score. There were no significant histopathological differences between the two groups. The features of LTG‐associated DIHS/DRESS and DIHS/DRESS due to other drugs differ.